If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1(4x + -3) = 4 Reorder the terms: 5x + -1(-3 + 4x) = 4 5x + (-3 * -1 + 4x * -1) = 4 5x + (3 + -4x) = 4 Reorder the terms: 3 + 5x + -4x = 4 Combine like terms: 5x + -4x = 1x 3 + 1x = 4 Solving 3 + 1x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 1x = 4 + -3 Combine like terms: 3 + -3 = 0 0 + 1x = 4 + -3 1x = 4 + -3 Combine like terms: 4 + -3 = 1 1x = 1 Divide each side by '1'. x = 1 Simplifying x = 1
| 5x+(4x+3)=4 | | 1+2(8a-3)=107 | | 8+4w=21+3w | | 20x^2+66x-14= | | -4h+14=46+4h | | s/-6-21=-28 | | 3(-5-3y)+2y=6 | | 6/g=7/15 | | Y=7x+17 | | 2y=4x-10 | | 35/20=7/v | | 6x^2-25x-9= | | 3r+7+5r= | | 5(6x+4)=10 | | -5x^2-10x-24=0 | | -5-9y+2y=6 | | 4*4-(3*4+6)= | | 4*4-(3*4+6)=-2 | | -x+7=22 | | y=3x+27 | | 3x-(4x-2)=12 | | M=6h | | 26/5=52/n | | 6g+3=39 | | 7x-10.75=6.8n+0.95 | | 26/5=52n | | 2/5(5+10m)=22 | | x^2+x=2x+6 | | 7/23+32/46+40 | | 3x-5-2x+3=13 | | 4b+6-2b+10=b+100 | | -24=u*6 |